Exploration of different solid variants of the anticancer medication Panobinostat (PNB) with improved physicochemical attributes - Kenguva, Gowtham; Giri, Lopamudra; Rout, Smruti Rekha; Acharya, Achyuta Nanda; Dandela, Rambabu (Journal of Molecular Structure, 2023)
Panobinostat (PNB), is a medication used for the treatment of multiple myeloma. It is a BCS Class II drug with strong permeability and poor solubility. Therefore, it is highly desirable to investigate novel PNB variants with improved physiochemical properties. In this regard, several solid forms of PNB have been produced employing mechanochemistry and solution crystallisation techniques using a variety of GRAS (Generally Recognized as Safe) salt formers, notably oxalic acid (OA), fumaric acid (FA), maleic acid (MA), and succinic acid (SA). Powder X-Ray Diffraction (PXRD), Single Crystal X-Ray Diffraction (SCXRD), and thermal analysis such as Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to characterize all the synthesised molecular adducts. Hirshfeld surfaces and fingerprint plots demonstrate that the molecular entities are stabilized by O & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;H, C & BULL;& BULL;& BULL;C and H & BULL;& BULL;& BULL;H intermolecular interactions. Moreover, the solubility of parent PNB and its molecular adducts in pH 1.2/pH 6.8 was evaluated at room temperature. In every instance, an increase in the solubility of molecular salts relative to the parent medication is seen, notably PNB.MA exhibits enhanced solubility of 0.294 mg/ml, a 73fold increase over the parent PNB. Furthermore, it is observed that this upsurge in solubility of all the forms is static at pH 1.2. A thorough analysis of the recovered residue after solubility showed that most of the molecular adducts were stable at pH 6.8 and did not display any phase change or dissociation (with the exception of PNB.MA), but at pH 1.2 they transferred into a new stable form and extensive analysis confirmed that it converted into PNB.Cl salt. To the best of our knowledge, this is the first report on novel solid forms of PNB with enhanced physicochemical properties which implies that the obtained PNB molecular adduct may help in the development of improved PNB formulations.
Keywords: Hydrogen bond; Molecular adducts; solubility; Solvates

Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.

New binary adducts of panobinostat with different carboxylic acid based NSAIDs: structural analysis and physicochemical properties investigation - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Shaikh, Tabrez R.; Jadab, Madhusmita; Pal, Satyanarayan; Dandela, Rambabu (ChemistrySelect, 2024)
Adoption of multitarget, cost-effective fixed-dose medication combinations can help lower the pill load without increasing the risk of adverse events. In this study, three new 1:1 drug-drug binary solid forms of panobinostat (PNB) and nonsteroidal anti-inflammatory drugs (NSAIDs) were effectively synthesized by liquid-assisted grinding and slow evaporation crystallization techniques. The obtained solid forms were extensively characterized by various analytical techniques. The structural investigation revealed that all molecular adducts formed salt with a comparable R42\${\textbackslashmathrm{R}}_4<\^>2\$(10) graph set pattern created by heteromeric interactions formed between PNB and corresponding salt formers. To determine the dissolving behavior of the newly developed adducts, solubility tests were performed at various pH levels (pH 1.2 and pH 7), and the results indicated that the solubility of all forms is increased at pH 7.0, particularly PNB.NIF has a solubility of 0.195 mg/mL, which is seven times higher than the parent drug. Furthermore, PXRD was used to assess the stability of the synthesized adduct at varied temperature and humidity levels and it was found that all the adducts are stable. Based on the findings, we hope that the newly found PNB drug-drug binary adducts have possible potential to broaden the use of drug combinations without changing the chemical structures.
Keywords: Drug-drug salts; Heteromeric interactions; Hydrogen bond; Non-steroidal anti-inflammatory drugs; Panobinostat

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility